Foliar anatomical characterization of four species Cuericí, Costa Rica - Ortiz Crúz, Maria Victoria (2021)
Introduction: The montane cloud forests of Costa Rica are one of the ecosystems with the greatest diversity and abundance of orchids, due to the continuous or seasonal presence of cloud cover over the vegetation. Anatomical features are important characters for identification and classification within Orchidaceae and help to understand trends in evolution. Objective: To characterize the foliar anatomy of four species of epiphytic orchids in the Cuericí cloud forest, Costa Rica to expand the knowledge about the foliar characters associated with the epiphytic habit. In addition, their relationship with the abiotic factors of the environment where they live was analyzed to elucidate possible adaptations of these species. Methods: The evaluated characters were cuticle thickness, leaf type according to stomatal distribution, mesophyll type and presence of sclerenchyma fiber bundles. Results and discussion: All species have foliar anatomical characters related to montane cloud forests, only in Camaridium wrightii some xerophytic features were observed. Conclusions: the thickness of the cuticle and the position of stomata between species possibly varied as a function of environmental conditions. The largest epidermal cells observed on the adaxial surface of the leaf in Stelis sp. and Masdevallia walteri may be related to the absence of pseudobulbs. Sclerenchyma fiber bundles were observed in the mesophyll of Camaridium wrightii, which gives the leaves mechanical resistance.